Sweden : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight Framework and Management. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Sweden in the areas of the systemic risk oversight framework and management. To promote accountability, the law should clarify the allocation of macroprudential powers between the government and the Finansinspektionen (Financial Supervisory Authority, FI) and grant the FI a clear legal mandate for macroprudential policy, with full operational independence. The Financial Stability Council, or a similar body-excluding the Ministry of Finance-should have the legal authority to issue recommendations, preferably with a 'comply or explain' approach. The law should also ensure that the Sveriges Riksbank's expertise in financial stability analysis finds a clear institutional role in the oversight of systemic risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet